Expression of B-cell activating factor, a proliferating inducing ligand and its receptors in primary central nervous system lymphoma - Tobias Birnbaum; Sigrid Langer; Sigrun Roeber; Louisa von Baumgarten; Andreas Straube (Neurology International, 2013)
B-cell activating factor belonging to the tumor necrosis factor family (BAFF) and a proliferating inducing ligand (APRIL) might play an important role in the pathogenesis of systemic B-cell malignancies. However, the BAFF/APRIL system has not been systematically evaluated in primary central nervous system lymphoma (PCNSL) to date. We assessed the expression of BAFF, APRIL and its receptors BAFF-R (BAFF receptor), BCMA (B-cell maturation antigen) and TACI (transmembrane activator and calcium modulator cyclophilin ligand interactor) in five PCNSL specimens by immunohistochemical staining. We found extensive expression of BAFF and weak to moderate expression of APRIL, BAFF-R, BCMA, and TACI in all specimens. CD20 positive cells showed expression of both ligands and receptors at the same time. Our results indicate that autocrine stimulation of the BAFF/APRIL system might be involved in the pathogenesis of PCNSL.